Some correlates of body dissatisfaction in urban school students - A. V. Pogodina; T. A. Astakhova; L. N. Lebedeva (Acta Biomedica Scientifica, 2024)
Background. Body dissatisfaction is widely spread among the population. It negatively affects human health, contributing to the development of eating disorders, anxiety and depressive disorders, and the formation of unhealthy eating patterns and lifestyle. Determining the factors associated with body dissatisfaction in adolescents may be important for the prevention of the above mentioned disorders.The aim of the work. To describe the prevalence, characteristics and factors associated with body dissatisfaction among urban school students.Materials and methods. Tenth-grade school students (n = 440) underwent anthropometry and also filled out questionnaires including socio-demographic factors and lifestyle factors. Collins scales were used to assess body dissatisfaction, and the Russian version of the Paediatric Quality of Life Inventory (PedsQL 4.0; Lyon, France) was used to assess health-related quality of life.Results. 60.2 % of school students reported a desire to have body figures different from the actual one. 42.7 % of adolescents experienced mild body dissatisfaction, 17.5 % experienced moderate and severe body dissatisfaction. The frequency of body dissatisfaction was comparable among both male and female adolescents, but it was more pronounced among girls compared to boys (Z = 2.2; p = 0.029). Boys were significantly more likely than girls to strive for larger body figures than what they felt they had (38.8 % vs. 8.1 %). In contrast, girls were significantly more likely than boys to want to lose weight (55.4 % vs. 12.3 %). Statistically significant associations with moderate/severe body dissatisfaction are shown for overweight/ obesity and for the time spent by schoolchildren watching TV, on social networks, and in the Internet. Sports activities demonstrated a protective role in relation to body dissatisfaction. The presence of body dissatisfaction significantly reduced all aspects of adolescents’ quality of life.Conclusions. The results of the study justify the approach to body dissatisfaction as an independent problem that requires active diagnostics and targeted exporure, and determine possible directions for preventive measures among adolescents.